Prophetic leadership and employee well-being: Gratitude as a mediator - Budiharto, Sus; Pratiwi, Yulizta Putri (HUMANITAS published by Universitas Ahmad Dahlan., 2025)
This study investigates the role of gratitude as a mediator in the relationship between prophetic leadership and employee well-being. The participants comprised 146 employees (118 males; 28 females) from a sharia financial institution in Yogyakarta. Measurement instruments included the prophetic leadership scale, the Islamic Gratitude Scale (IGS-10), and the Employee Well-Being Scale (EWBS). Mediation analyses were employed for data examination. Results indicated that gratitude fully mediates prophetic leadership and employee well-being (indirect estimate = 0.12; p<0.01). Employees who perceive their leaders as embodying prophetic qualities tend to experience higher levels of gratitude, enhancing their well-being within the organization. These findings have significant practical implications, suggesting that organizations can foster employee well-being by promoting gratitude and improving their leaders’ prophetic leadership capacities.